Ecologia alimentar de onca-pintada (Panthera onca Carnivora, Felidae) e a influência da sazonalidade e heterogeneidade de hábitats em duas áreas no Pantanal Sul-Matogrossense, Brasil - Guilherme Leandro Castro Corrêa (2015)
jaguar, the largest neotropical cat, now has a more restricted distribution than the original, but the Pantanal region is nevertheless home to substantial populations of the species. In this region, the plains seasonal flooding is the main fator that controls the potential prey availability for this predator. Beyond that, due to its economy is based on farming, the Pantanal is subject to constant expansion of human activities that directly impact the jaguar populations. To improve the cats conservation and biology knowledgement in the region, this study aims to compare the diet of jaguar between areas with different habitat heterogeneity degrees and the influence of seasonality on diets occurring within each of these areas. Between 2005 and 2010, we have collected opportunistically scat samples in two farms of Pantanal in Mato Grosso do Sul, Brazil, with different extents of natural and man-made habitat classes. We have described and evaluated the consumed prey community composition between those two farms. Moreover, we have tested the hypothesis that there is a composition difference between the dry and wet seasons for each farm. Both the seasonality and the proportion of anthropic matrices in the landscape have showed as important factors in changing the composition of consumed prey by jaguar.